The Influence of Industry 4.0 and Firm’s Level Characteristics Toward Business Model Innovation and Its Impact on Performance - Iskandar, Donant Alananto; Wahyudi, Triyono Arief (International Journal of Educational Technology and Artificial Intelligence, 2024)
companies compete with others which are not only within industry. Therefore managers should have the valuable orientation in managing their resources to achieve the competitive advantage through creating innovation performance. This research offers entrepreneurial marketing as this valuable orientation. The objective is to analyze the effect of entrepreneurial marketing on managing resources and also to analyze the influence of managing resources on innovation performance. It is quantitative research which has a conceptual model consisting of three constructs. These were entrepreneurial marketing, managing resources and innovation performance. There are 2 hypotheses. The unit of analysis was the managerial level of manufacturing companies. The data is collected through distributed questionnaires. The collected questionnaire is 91 out of 215 distributed questionnaires. The data set is analyzed by using the SPSS (Statistical Package for the Social Sciences) for reliability test, validity test, normality test and hypothesis tests. The results are all hypotheses supported by the data. The contribution on theoretical manner is the empirical evident of the effect of entrepreneurial marketing on managing resources and also the effect of managing resources on innovation performance. The managerial implication of this research is the entrepreneur could creatively explore entrepreneurial marketing’s elements which are proactiveness, opportunity focus, calculated risk taking, innovativeness, customer intensity, resource leveraging and value creation to manage resources for achieving the best innovation performance.